Corporate social responsibility for a sustainable inclusive growth in India - Mishra, R.K.; Singh, Punam; Sarkar, Shulagna (Journal of Management and Development Studies, 2013)
Corporate Social Responsibility (CSR), Inclusive growth and Sustainability are essential aspects of the core strategy and business practices for cutting edge organizations. Sustainable development and CSR as an agenda, have matured rapidly, and is driven by demand for greater accountability by corporate to society in India. Views on corporate responsibility have contributed to mounting pressure on business to demonstrate its social accountability. The paper is aimed at formulating a conceptual framework for sustainable inclusive growth and also elaborates the CSR areas of Oil and Gas Central Public Sector Enterprises (CPSE’s) in India for sustainable inclusive growth. The paper is based on secondary data and focuses on highlighting the CPSE approaches to CSR in the pre and post implementation of CSR guidelines in India. The paper also discusses cases demonstrating innovation by Indian companies to bring in sustainable inclusive growth.